ANALYSIS OF OPTICAL DENSITY OF ELECTROSTATIC SPRAY ON APPLE IN WINTER AND SUMMER SEASON - Mr. D.R.Jadhav ,; Dr. V.S. Majali,; Mr.A. I. Sawant , (International Journal of Innovations in Engineering Research and Technology, 2021)
Wastage of agricultural chemicals and ensuing environmental pollution is an issue, where ineffectivespray deposition is a major concern with conventional pesticide application methods. Electrostaticspraying is known to be one of the most effective methods to improve frontsurface deposition,backsurface deposition, overall deposition, and distribution on the plant targets. Deposition of charged sprays on front and back surfaces with and without electrostatic on apples in winter and summer season was studied in the laboratory. An air-assisted electrostatic induction spray charging system was used toapply charged spray at uniform application (ground) speeds.Spray deposition is determined by using a fluorescent tracer technique. The droplet velocityand charging voltage were the key factors for obtaining desired spray deposition on apples. .